Expression of Biofilm-Degrading Enzymes in Plants and Automated High-Throughput Activity Screening Using Experimental Bacillus subtilis Biofilms - Opdensteinen, P.; Dietz, S. J.; Gengenbach, B. B.; Buyel, J. F. (Frontiers in Bioengineering and Biotechnology, 2021)
Biofilm-forming bacteria are sources of infections because they are often resistant to antibiotics and chemical removal. Recombinant biofilm-degrading enzymes have the potential to remove biofilms gently, but they can be toxic toward microbial hosts and are therefore difficult to produce in bacteria. Here, we investigated Nicotiana species for the production of such enzymes using dispersin B-like enzyme Lysobacter gummosus glyco 2 (Lg2) as a model. We first optimized transient Lg2 expression in plant cell packs using different subcellular targeting. We found that expression levels were transferable to differentiated plants, facilitating the scaling up of production. Our process yielded 20 mg kg-1 Lg2 in extracts but 0.3 mg kg-1 after purification, limited by losses during depth filtration. Next, we established an experimental biofilm assay to screen enzymes for degrading activity using different Bacillus subtilis strains. We then tested complex and chemically defined growth media for reproducible biofilm formation before converting the assay to an automated high-throughput screening format. Finally, we quantified the biofilm-degrading activity of Lg2 in comparison to commercial enzymes against our experimental biofilms, indicating that crude extracts can be screened directly. This ability will allow us to combine high-throughput expression in PCPs with the novel activity assay.